2013
DOI: 10.1590/s0034-8910.2013047004410
|View full text |Cite
|
Sign up to set email alerts
|

Material particulado originario de queimadas e doencas respiratorias

Abstract: OBJECTIVE:To analyze the effects of exposure to fi ne particulate matter from burning on hospital admissions due to respiratory diseases in children and the elderly. METHODS:This is an ecological time series study that took place in the city of Cuiaba, Mato Grosso, in Brazil's Amazon Region, in 2005. Information on the daily levels of fi ne particulate matter PM 2.5 was made available by the Brazilian National Institute for Spatial Research. The model included variables related to temperature, relative humidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2
31

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 14 publications
1
32
2
31
Order By: Relevance
“…The use of data estimated by the CCATT-BRAMS model has been described by some authors, like Silva et al 17 , also in Cuiabá. These authors found an association between exposure to PM 2.5 and hospitalizations at lags 1, 2, and 5 for the entire year, and at lags 1, 5, and 6 in the dry season (second semester), as a function of a 10μg/m 3 increase in this pollutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of data estimated by the CCATT-BRAMS model has been described by some authors, like Silva et al 17 , also in Cuiabá. These authors found an association between exposure to PM 2.5 and hospitalizations at lags 1, 2, and 5 for the entire year, and at lags 1, 5, and 6 in the dry season (second semester), as a function of a 10μg/m 3 increase in this pollutant.…”
Section: Discussionmentioning
confidence: 99%
“…This model is used operationally by the Center for Weather Forecasting and Climate Studies of the Brazilian National Institute for Space Research (CPTEC/INPE) in an operational base. It estimates PM 2.5 concentrations every three hours, resulting in eight estimates made by the model at 40m aboveground, with a resolution of 25x25km 13,14 ; Recent applications of data estimated by CCATT-BRAMS in epidemiological studies can be found in César et al 15,16 , Silva et al 17 , Nascimento et al 18 , and Carmo et al 19 .…”
Section: Introductionmentioning
confidence: 99%
“…É importante ressaltar que esta cidade não conta com estações medidoras da CETESB e assim foram utilizados dados estimados pelo modelo matemático CATT-BRAMS . O uso dos dados estimados por esse sistema, validados por outros autores (Ignotti et al, 2010;César et al, 2013;Silva et al, 2013) Os valores médios obtidos por modelagem matemática para as concentrações dos poluentes apresentaram-se bem abaixo dos valores encontrados por Gouveia et al (2006) utilizando dados obtidos de 14 estações de monitoramento da CETESB na cidade de São Paulo, mas os efeitos na saúde, representados por risco de internação por doenças respiratórias, segundo exposição aos óxidos de nitrogênio, foram maiores para internação por DRs em todas as idades, que os encontrados no estudo acima citado, mesmo considerando um aumento de 10 µg/m 3 nas concentrações de NO 2 . Outro ponto a ser citado é que as concentrações não ultrapassaram os limites recomendados, não ocorrendo nenhum dia com qualidade do ar que não fosse considerada "boa", segundo os valores padrões estabelecidos pela CETESB (2013).…”
Section: Resultsunclassified
“…O município de Taubaté, considerando-se as áreas urbana e rural, mede aproximadamente 17 x 25 km e a área urbana, onde se concentra a maior parte da população, mede aproximadamente 8 x 7 km. Apesar da existência de um conflito de resolução espacial entre o que o modelo é capaz de representar e a área de abrangência da população exposta aos poluentes, estudos empregando os dados estimados gerados pelo CATT-BRAMS têm sido publicados por revista de impacto na literatura internacional, demonstrando a aceitação da aplicação destes dados estimados no monitoramento dos efeitos dos poluentes atmosféricos sobre doenças respiratórias (Ignotti et al, 2010;Silva et al, 2013;César et al, 2013).…”
Section: Methodsunclassified
See 1 more Smart Citation